The life cycle of a CEO : the myths and truths of how leaders succeed - Hildebrand, Claudius A.; Stark, Robert J. (UK: John Murphy Press, 2024)
"Claudius Hildebrand and Robert Stark, two key figures at Spencer Stuart, the world's most influential executive search firm, combine unprecedented research-analyzing the individual performance of every twenty-first century CEO of the S&P 500 and accompanying macroeconomic and industry cycles - with 100 in-depth interviews to reveal the distinctive life cycle of a CEO. These life cycles are predictable passages of headwinds and tailwinds that leaders must face at each stage of their tenure, from the day they walk through the door till the day they walk out. Hildebrand and Stark reveal how successful CEOs navigate these cycles by developing fresh skills and strategies needed for each distinct passage. As captains of organizations crucial to the economic foundation of our society, CEOs have a critical role to play. But our understanding of why some drive phenomenal innovation and growth and others quickly falter is clouded by myths and caricatures perpetrated by the media, Wall Street, political and social commentators: The bewildered rookie; the rock star who can do no wrong; the corporate savior, parachuting in to restore former glory; the treacherous villain out to destroy the planet or exploit people. Hildebrand and Stark break through these myths and provide insight into how those who thrive push themselves to evolve and master skills for meeting the challenges their companies face, and how they navigate the inevitable personal and organizational crises of corporate life as performance waxes and wanes. This invaluable roadmap for personal growth yields insight needed for navigating crises such as: criticism by stakeholders; when leaders are at the greatest risk of stagnation and firing; and when aversion to risk is likely to turn into a weakness. It provides the foundation for both rookies and seasoned leaders to gain self-insight and self-confidence and unlock both higher individual and corporate performance"--
Includes bibliographical references and index.
Keywords: Chief executive officers; Success in business